Africa RISING-Spraying Regime Effects on the Grain Yield of Cowpea Varieties in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2016)
Project title: Africa RISING-Spraying Regime Effects on the Grain Yield of Cowpea Varieties in Northern Ghana. Project abstract: The data set evaluate adaptability and suitability of cowpea varieties to different ecozones. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa/